FRONT-HAND-PUNCH SPEED IMPROVEMENT EXPERIMENTAL METHODOLOGY IN KARATE - Radoslav Penov; Milen Chalakov (Scientific Publishing House. NSA Press, 2018)
This article presents the development of an experimental methodology that aims to improve the speed of the front-hand punch in karate. The rationale behind developing this methodology is that the speed of the front-hand punch in karate is one of the most important criteria for the successful defeat of the opponent. In addition, the front-hand punch is one of the most commonly used punches during matches. The objective that we set was to study the effect of the application of the methodology we developed for the purpose of improving the speed of the front-hand punch (Kizami Tsuki) in karate. To accomplish this study, we used a computerized video system to register and analyze the speed of karate punches performed by the participants in the experiment. The results regarding the speed of the straight-hand punch were measured in the same way in order to provide identical conditions. Input data was processed by means of applied software for kinematic analysis. To prove the credibility of the registered data, we used statistical analysis methodology. We hope that by presenting our methodology in this article, more coaches will begin to use modern tools and methods in order to improve the quality of training in karate.